Studi Ketahanan Bahasa Mandobo Atas [AAX] dan Mandobo Bawah [BWP] - Andreas Tricahyadi (Ranah: Jurnal Kajian Bahasa, 2024)
The Upper Mandobo [aax] and Lower Mandobo [bwp] languages, as minority languages, are vulnerable to extinct, especially if the government does not concern to promote the learning and use of the languages. On the other hand, Indonesian Language and South Papuan Malay are becoming stronger, because these languages are taught in schools and used in the daily life and economic transaction. Therefore, this paper would like to research the language vitality of Upper Mandobo and Lower Mandobo, that is exposed to those condition. The research method used Participatory Approach Method, with Wheel of Vitality as the survey tool, combined with EGIDS (Expanded Graded Intergenerational Disruption Scale). The data collection technique used purposive sampling and the analysis technique used qualitative approach. The research result, we found the vitality is decreasing to EGIDS 6b (endangered) for Upper Mandobo and EGIDS 7 (shifting) for Lower Mandobo. Follow up recommendations are language development for Upper Mandobo and language documentation for Lower Mandobo AbstrakBahasa Mandobo Atas [aax] dan Mandobo Bawah [bwp], sebagai bahasa minoritas, memiliki kerentanan untuk punah, terlebih tanpa adanya perhatian dari pemerintah untuk mempromosikan pembelajaran dan penggunannya. Sebaliknya, Bahasa Indonesia dan Melayu Papua Selatan menjadi makin kuat, sebab bahasa tersebut diajarkan di sekolah dan digunakan sehari-hari dan dalam transaksi ekonomi. Paper ini ditujukan untuk mengkaji kembali ketahanan bahasa Mandobo Atas dan Mandobo Bawah. Metode penelitian yang digunakan adalah pendekatan partisipatoris, dengan alat survei roda ketahanan bahasa yang dipadukan dengan EGIDS (Expanded Graded Intergenerational Disruption Scale). Teknik pengumpulan data menggunakan purpossive sampling dan teknik analisis menggunakan pendekatan kualitatif. Dari analisis hasil temuan, diperoleh bahwa terdapat penurunan ketahanan bahasa menjadi EGIDS 6b untuk Mandobo Atas dan EGIDS 7 untuk Mandobo Bawah. Rekomendasi untuk menindaklanjuti pemeliharaan bahasa tersebut adalah pengembangan bahasa untuk Mandobo Atas dan dokumentasi bahasa untuk Mandobo Bawah.